2012
DOI: 10.5603/fhc.2011.0050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ursolic and oleanolic acids on human skin fibroblast cells

Abstract: Abstract:In this article, we look at how ursolic and oleanolic acids can be used for the purpose of quality control of natural products used in dermatocosmetology as well as of various other therapeutic preparations. Ursolic acid (UA) and oleanolic acid (OA) are pentacyclic triterpenes and they are constituents of many medicinal herbs. In this study, we analyzed the cytotoxic and anti-proliferative activity of OA and UA against normal human skin fibroblasts (HSF). Additionally, the scavenging activity of free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…In accordance with this conclusion. Martin et al observed disrupted stress fibers in a human astrocytoma cell line after oleanolic acid treatment [87], whereas the same compound showed no alteration of cytoskeletal structures in primary human dermal fibroblasts [88], supporting our findings in primary keratinocytes.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with this conclusion. Martin et al observed disrupted stress fibers in a human astrocytoma cell line after oleanolic acid treatment [87], whereas the same compound showed no alteration of cytoskeletal structures in primary human dermal fibroblasts [88], supporting our findings in primary keratinocytes.…”
Section: Discussionsupporting
confidence: 89%
“…Intriguingly, OA and its derivatives has no cytotoxicity to normal human cells [15], [16]. These inhibitory effects of OA are involved with its suppression of some specific intracellular signaling pathways, such as STAT3, JNK, Akt and NF-kappaB signaling pathways [10], [12], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Factin has also been implicated to play a key role in cell migration and wound healing [23]. In line with these studies, a recent evaluation of compound toxicity on HDF has demonstrated the correlation between actin polymerization and cytotoxic and anti-proliferative activity [24]. Additionally, the level of polymerized actin has been demonstrated to follow the ageing process with higher expression of F-actin in HDF from aged donors compared to younger ones [25].…”
Section: Introductionmentioning
confidence: 88%